Microprocessor-Based System for Identifying Oversizes in Railway Transport - Kurbanov, Janibek F.; Yaronova, Natalya V.; Khidirov, Erkin I. (International Russian Automation Conference (Online), 2024)
The article contains information about the most important conditions for ensuring the safety of train traffic, namely the size of the rolling stock. The dimension is the maximum external geometric outline of structures and devices, which allows one to determine the space they occupy and the conditions for the placement of neighboring objects. Locomotives and railway carriages must pass freely along the railway track past various kinds of track structures, station platforms, buildings and other devices, and not touch the rolling stock located on adjacent tracks and various artificial structures. In this article, a microprocessor device is developed based on modern elements for controlling and determining the gauge of the automatic and telemechanic system of the railway sections. In order to determine the abnormality of the movement structure, the information was received to the microprocessor device using infrared sensors, and the complete management and control of the process was achieved with the help of the created software. A structural scheme has been developed for connection to the electrical centralization systems of the created device.